Association between Mosquito Coils Use with Nasopharyngeal Carcinoma - Witri Septiani; Yussy Afriani Dewi; Irvan Afriandi (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2020)
Introduction: Nasopharyngeal carcinoma (NPC) is a malignancy of squamous cells on the nasopharyngeal epithelial layer and is the most common otorhinolaryngology malignancy found in Indonesia. The etiology of NPC is multifactorial, including food, environment, genetics, and Epstein-Barr virus infection. Mosquito coils contain volatile carcinogens, such as formaldehyde and acetaldehyde, which may cause malignancy on upper respiratory tract epithelial cells. Objectives: The study aimed to understand the association between mosquito coils use with the incidence of nasopharyngeal carcinoma. Methods: This was a hospital-based unmatched case-control study design involving 80 patients on the Oncology Clinic of Department of Otorhinolaryngology-Head and Neck Surgery at Dr. Hasan Sadikin General Hospital from September to October 2015. The questionnaire about NPC risk factor exposure, including the history of mosquito coil use, was applied as a study instrument. Statistical analysis used the chi-square test to acquire the association between two categorical variables and was considered significant if P-value is <0.05. Results: The percentage of mosquito coil users in the case group (52.7%) was higher than in the control group (30%). Statistical analysis using the chi-square test revealed P = 0.041 with OR (CI 95%) equals 2.58 (1.03-6.45). This result showed that mosquito coil use might increase the risk of nasopharyngeal carcinoma incidence by 2.58-fold. Conclusion: There is an association between mosquito coils use with nasopharyngeal carcinoma.